IMPLEMENTASI DAN PENGUJIAN WEBSITE E-TRAINING MENGGUNAKAN USER ACCEPTANCE TESTING (UAT) - Ganda Yoga Swara (Ensiklopedia Research and Community Service Review, 2026)
Abstract: This study aims to implement and test a website-based system using the waterfall model. This e-training website was developed as a web-based learning platform that provides materials, learning videos, practice questions, quizzes, projects, and evaluations that can be accessed anytime and anywhere. In addition to supporting the learning process, this website also functions as a self-training tool for students to improve their understanding of E-Commerce materials. This website was built with the CodeIgniter3 framework and uses the PHP, CSS, JavaScript programming languages, MySQL database, and the Apache web server. The results of black box testing showed valid results with a 100% success rate. The results of the User Acceptance Testing (UAT) test obtained showed that 82.5% of users agreed with the e-training website. Therefore, it can be concluded that this system is feasible to use.Keywords: E-Training, Blended Learning, E-Commerce, Website, User Acceptance Testing.